FDIs and commercial balance in CEE countries: Special focus on the manufacturing economic sectors : a VAR analysis - Magdalena Rădulescu; Gabriela Cirstea Cornelia; Lucian Aron Belascu (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2020)
Purpose: Some empirical findings of the role of foreign direct investment (FDIs) in a host country's export performance was found by many researchers, since exports have been for a long time viewed as an engine of economic growth. But exports and imports are inter-correlated and some works proved that sometimes, the foreign-owned companies import more than they export in some economic sectors. The paper aims to establish the relation between total FDIs and the commercial balance (goods) and between FDI stocks in the manufacturing economic sectors and the commercial balance of manufactured goods in 11 Central and Eastern European countries during the crisis period and post-crisis period (2009-2018). We have tested the causality using Granger causality test to see if there is a uni-directional or bi-directional causality between those variables. We have tested for co-integration and we haven't found a long-term relationship between those variables and we have applied the VAR technique. Our results have proved a bi-directional causality between FDI stockexports-imports and a stronger impact of FDIs stock on the trade balance of manufactured goods than the impact of total FDI stock on the commercial balance of goods in CEE countries. Design/methodology/approach: Granger causality tests, cointegration test, VAR analysis Finding: We have found no cointegration in the long-run between FDIs stocks and exports and imports in the CEE countries. We have found a bi-directional causality between those variables. We have found a stronger impact of FDIs stock on export and imports of manufactured goods than the impact of FDIs stock on total exports and imports in the CEE countries. Research limitations/implications: This research can be extended analysing a longer period of time and including more exogenous variables in the analysis such as labour productivity, labour cost and GDP growth. It can also be performed a panel analysis. The CEE countries should design adequate policies in order to attract more FDIs in the manufacturing sectors, given the strong impact of FDI stock for these sectors and given the large share of the manufactured goods of the total exports of the CEE countries. Originality/value: This research is important for CEE region because of the large share of the manufactured good of the total exports of these economies.
Keywords: F14; F21; L60; 330; commercial balance; manufactured goods; FDI stock; CEE countries